2006
DOI: 10.1124/jpet.105.099184
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Urothelial Stretch-Induced Cyclooxygenase-2 Expression in Novel Human Cell Culture and Porcine in Vivo Ureteral Obstruction Models

Abstract: Obstruction and stretch induce cyclooxygenase (COX)-2 expression and prostanoid synthesis in urinary tissues, causing pain, inflammation, hypercontractility, and cell proliferation. Our objective was to characterize acute COX-2 induction during in vivo ureteral obstruction, establish a cell culture model of urothelial stretch-induced COX-2 expression, and evaluate whether mechanotransduction could alter transcriptional and post-transcriptional regulation of COX-2. We performed laparoscopic unilateral ureteral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…The same study showed a four-fold induction in COX-2 expression after 6 hours of acute ureteral obstruction in swine ureters harvested ex vivo. 11 In a similar study using mice subjected to unilateral ureteral obstruction, COX-2 levels in whole ureteral tissue extracts were increased nine-fold after 6 hours compared to unobstructed controls. 10 …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The same study showed a four-fold induction in COX-2 expression after 6 hours of acute ureteral obstruction in swine ureters harvested ex vivo. 11 In a similar study using mice subjected to unilateral ureteral obstruction, COX-2 levels in whole ureteral tissue extracts were increased nine-fold after 6 hours compared to unobstructed controls. 10 …”
Section: Discussionmentioning
confidence: 94%
“…The elevated expression levels were comparable to what has previously been reported after several hours of ureteral obstruction. 8,9,11 Furthermore, this effect persisted after 2 hours of rest and reperfusion before tissue sampling was performed. To our knowledge this is the first study showing such a substantial impact on COX-2 and TNF-α expression in the ureter by what may be characterized as a minimal surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and experimental studies have demonstrated that COX-2 is upregulated in conditions associated with glomerular inflammation including acute glomerulonephritis and ureteral obstruction [29,30,31]. In addition, recent experimental studies have also demonstrated that COX-2 expression is upregulated in experimental models of diabetes [32, 33] and chronic kidney disease [34, 35] and that COX-2 inhibition in a model of renal ablation reduces mesangial matrix expansion, glomerular sclerosis and fibronectin and collagen IV expression, suggesting that COX-2-derived prostaglandins play an important role in the pathogenesis of renal injury [36].…”
Section: Discussionmentioning
confidence: 99%
“…Our in vivo findings are therefore physiologically comparable to leukocyteindependent mechanisms of COX-2 expression observed during human UTO. 16 We further showed that PI3K signaling is upstream of both stretch-induced PKCζ activation and stretchinduced COX-2 expression during urothelial cell stretch.…”
Section: Discussionmentioning
confidence: 96%
“…The final published version may differ from this proof. 16 16 stretch-induced PKCζ activation ( Figure 5C). These results indicate that both stretch-induced PKCζ activation and COX-2 expression are PI3K-dependent.…”
Section: Stretch-induced Pkcζ Activation Is Pi3k-dependentmentioning
confidence: 90%